Pemanfaatan Film Pendek “Fixer” sebagai Alat Untuk Menggambarkan Dehumanisasi Akibat Kemajuan Teknologi - Alvikha Adrian; Yuyun Anggraini; Dendy Muris (Puslitbang Sekawan Institute Nusa Tenggara, 2020)
The ability to think is the defining factor that sets apart human beings and any other creations.By using their minds and their mental capacity, humans try to assign meaning to get a betterunderstanding of the phenomenon and things in their surroundings. Humans gave birth toscience and technology as a means to solve their problems and in process, fulfilling specificneeds. Thus, human beings began to live side by side with technology. As time has progressed,technology also shapes what values to uphold. Advancement in technology often gives a newperspective on life. We saw a possibility of losing the essence of “what makes us human” dueto the irresponsible use of technology. Aside from being entertainment, this project also aimsas a means to convey the message that technology used wisely so as not to lose identity as ahuman being. This project manifests as a sci-fi short movie based on technologicaldeterminism and dehumanization, in which we made the audience think about what values wehave lost in exchange for technology. This project uses an action genre and a unique effect toconvey the world-building aspect. We hope the whole process of this project could serve as areference for any parties who want to create short movies within the same context.